Step-by-step explanation:
It is given that,
-2.2 × 3.7 = 8.14
The first number is -2.2
The second number is 3.7
We know that, (-) × (+) = - (the answer is a negative)
If we multiply -2.2 and 3.7, we will get -8.14.
But in the given case, the answer is 8.18 instead of -8.14. Hence, this is the only error.
Answer:2,2
Step-by-step explanation:
I remember doing this last year
We use the formula a^2 - b^2 = ( a - b )( a + b );
We have a = 5m - 2 and b = 3m - 4;
<span>(5m-2)^2-(3m-4)^2 = (5m - 2 -3m + 4) x (5m-2 + 3m - 4) = (2m + 2)(8m - 6) = 2(m +1) x 2(4m - 3) = 4(m+1)(4m-3);
</span>
Answer:
28
Step-by-step explanation:
Answer:
x = -4
Step-by-step explanation: